Structural and spectroscopic properties of AlN layers grown by MOVPE - Thapa, S. B.; Kirchner, C.; Scholz, F.; Prinz, G. M.; Thonke, K.; Sauer, R.; Chuvilin, A.; Biskupek, J.; Kaiser, U.; Hofstetter, Daniel (My University, 2007)
The effects on surface morphology, crystal quality, and growth rate of undoped AlN layers grown on c-plane sapphire substrates due to the changes in growth parameters, such as V–III ratio, N2–H2 ratio, and growth temperature in LP-MOVPE are studied here. The optimized growth process resulted in an almost flat surface morphology with a significantly reduced number of hexagonal pits (3 x 107 cm-2) and good crystalline quality having a rms value of roughness of 0.4 nm measured by atomic force microscopy and a high resolution X-ray diffraction (HRXRD) FWHM value for (0 0 0 2) reflection of 200 arcsecs. The threading dislocation density of the AlN layer is estimated approx. 109 cm-2 from cross-sectional transmission electron microscopy (TEM) measurements. Additionally, these optimized samples show a strong donor-bound exciton luminescence signal with a FWHM of 20 meV. Furthermore, small period AlN/GaN superlattice structures with excellent uniformity were grown, as proven by our HRXRD and TEM studies.